The effect of size and surface ligands of iron oxide nanoparticles on blood compatibility. Issue 13 (21st February 2020) - Liu, Tao; Bai, Ru; Zhou, Huige; Wang, Rongqi; Liu, Jing; Zhao, Yuliang; Chen, Chunying
Abstract : Due to the unique physicochemical properties, superparamagnetic iron oxide nanoparticles (SPIONs) have attracted increased attention, which show different effects on red blood cell, plasma, platelet, C3 complement and vascular endothelial cell. Abstract : Superparamagnetic iron oxide nanoparticles (SPIONs) have been widely used and have attracted increased attention for their unique physicochemical properties, especially in biomedical sciences as contrast agents following intravenous administration. However, only few studies have systematically reported the blood compatibility of iron oxide nanoparticles with different physicochemical properties such as different sizes and surface ligands. Therefore, we selected three widely used organic ligands (polyacrylic acid, hyaluronic acid, and chitosan) with modified SPIONs at the same size of 5–6 nm, and polyacrylic acid-modified SPIONs with different sizes (5, 10, and 30 nm) at different concentrations to evaluate their haemocompatibility. Our results revealed that SPIONs modified with polyacrylic acid demonstrated size-dependent destruction of red blood cells and complement activation. Interestingly, 5 nm SPIONs prolonged blood clotting time as compared with 10 nm and 30 nm SPIONs in vitro . Compared with polyacrylic acid-modified SPIONs, hyaluronic acid- and chitosan-modified SPIONs least affected red blood cells, platelets, coagulation, and complement activation. Hence, hyaluronic acid- and chitosan-coated SPIONs are more suitable for nanomedicine applications than polyacrylic acid-coated SPIONs. Furthermore, the interaction between SPIONs and blood components strongly correlated with the administered concentration of nanoparticles. These results will provide some experimental information for safe-by-design SPIONs.